Role of EZH2 in Epithelial Ovarian Cancer: From Biological Insights to Therapeutic Target - Li, Hua; Zhang, Rugang (Frontiers in Oncology, 2013)
EZH2 is the catalytic subunit of polycomb repressive complex 2 (PRC2), which generates a methylation epigenetic mark at lysine-27 residue of histone H3 (H3K27me3) to silence gene expression. EZH2 target genes are involved in a variety of biological processes such as stem cell pluripotency, cell proliferation and oncogenic transformation. EZH2 is often overexpressed in epithelial ovarian cancer cells and in ovarian cancer-associated stromal endothelial cells. Notably, EZH2 promotes cell proliferation, inhibits apoptosis and enhances angiogenesis in epithelial ovarian cancers. In contrast to genetic alterations, which are typically non-reversible, epigenetic alterations are reversible. Thus, inhibiting EZH2/PRC2 activity represents an attractive strategy for developing ovarian cancer therapeutics by targeting both ovarian cancer cells and ovarian tumor microenvironment. Here we discuss the progress recently obtained in understanding how EZH2/PRC2 promotes malignant phenotypes of epithelial ovarian cancer. In addition, we focus on strategies for targeting EZH2/PRC2 to develop novel epithelial ovarian cancer epigenetic therapeutics.